Night Vision: Blind Characters in John Gardner's Fiction - Sayers, Edna Edith (Disability Studies Quarterly, 2007)
American novelist and teacher John Gardner (1933-1982) grew up near the New York State School for the Blind in Batavia, a town that boasted a large and vibrant blind community up into the 1970s. This experience is surely why his novels include blind characters with fully imagined histories and inner lives, an extreme rarity in literary history. Esther Clumly in The Sunlight Dialogues, for example, is not only the presiding spirit of the novel but also a rounded and dynamic major character with a realistic blind-school background and a web of friends and community. What's remarkable is how Gardner controls the distance between his own views — that blind people are numerous, competent, interesting, and yet essentially ordinary — and those of his characters, some of whom find blind people frightening, pitiable, freakish, or stupid. This controlled distance creates tension, depth, and, sometimes, irony.